2020
DOI: 10.1111/1467-8268.12412
|View full text |Cite
|
Sign up to set email alerts
|

Ghana's national health insurance, free maternal healthcare and facility‐based delivery services

Abstract: Ghana implemented the National Health Insurance Scheme (NHIS) in 2005 and introduced free maternal healthcare (FMH) into the scheme in 2008. These reforms aimed at improving the utilization of healthcare, especially for expectant mothers. Using data from the 2008 and 2014 Ghana Demographic and Health Surveys (GDHS) with a sample of 8,081, this study employed multivariate probit and conditional mixed process (CMP) estimators to analyze the NHIS enrolment and the use of facility‐based delivery services among exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 30 publications
2
26
0
2
Order By: Relevance
“…Consequently, higher health services utilization in rural locations is not always a function of improved healthcare delivery system but a reflection of lack of choice for better alternatives. Indeed, other barriers to MNCH service utilization not explored in this study are acknowledged in terms of long travel times to health facilities [24,26,29], socio-cultural beliefs [16,23,30,31] and financial inaccessibility [32][33][34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, higher health services utilization in rural locations is not always a function of improved healthcare delivery system but a reflection of lack of choice for better alternatives. Indeed, other barriers to MNCH service utilization not explored in this study are acknowledged in terms of long travel times to health facilities [24,26,29], socio-cultural beliefs [16,23,30,31] and financial inaccessibility [32][33][34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…The high ANC and SBA in Ghana can be attributed to the interventions instituted by the Ministry of Health and the Government of Ghana over the past two decades. For instance, the NHIS and the free MCH policies have been instituted to enable the poor and less privileged in the country to be able to access MCH [ 16 , 17 ]. The low utilisation of PNC within 24 h could be as a result of healthcare providers not counselling women on the importance of PNC within the first 24 h. The study also observed that only a few proportions of women utilised all three components of MCH.…”
Section: Discussionmentioning
confidence: 99%
“…The National Health Insurance Scheme (NHIS), for instance, was effected in 2005 to cushion the poor [ 15 ]. The free MCH policy was subsequently added to the insurance scheme in 2008 to ensure that women who are subscribed to the insurance scheme enjoy all MCH services without any out-of-pocket payment [ 16 , 17 ]. Likewise, the Community-based Health Planning Services (CHPS) was introduced in 2008 to the fulfilment of the Universal Health Coverage (UHC) target and to reach persons in rural and remote locations with essential health care including maternal health services [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the pursuit of achieving the SDG target of UHC, many countries in sub-Saharan Africa (SSA) have implemented health insurance policies over the last two decades [4]. Many of the schemes currently cover public servants at both central and local government levels together with their family members while others cover the entire population [5][6][7][8][9][10][11][12][13][14]. The health insurance schemes in SSA have been introduced to largely replace the existing health financing systems which are dominated by out-of-pocket payments.…”
Section: Introductionmentioning
confidence: 99%